Hubungan promosi susu formula, produksi ASI dan psikologis ibu dengan pemberian ASI Eksklusif - Agustina Agustina; Irma Hamisah; Yulia Mutia (Politeknik Kesehatan Kemenkes Aceh, 2020)
Background: Giving breastmilk exclusively is very important for the health and development of infants. In Indonesia the scope of exclusive breastfeeding until the age of 6 months is still relatively low. This situation will have an impac on the quality of the nation’s next generation and also the national economy.Objectives: To obtain the relationship between the promotion of formula milk, Breastmilk production and psychological factor of mother with exclusive breastfeeding in the work area of the Bireuen Peusangan health center.Methods: This research is analytic descriptive with cross sectional approach. This research was conducted in the Peusangan Bireuen Community Health Center from 19 February-4 March 2018. The number of samples was 67 mothers who had babies aged 7-11 months. Data processing was carried out with SPSS and Chi-Square statistical test analysis with p-value < 0.05.Results: The results showed that 43 people (64.2%) gave exclusive breastfeeding, ther was relationship between exclusive breastfeeding and the promotion of formula milk (p= 0.032), Breastmilk production (p= 0.047), but not related to psychology (p=0,830).Conclusion: Breastmilk production and promotion of formula milk are related to exclusive breastfeeding.